Development of magnetically recyclable visible light photocatalysts for hydrogen peroxide production - Pal S.; Kumar S.; Verma A.; Kumar A.; Ludwig T.; Frank M.; Mathur S.; Prakash R.; Sinha I. (My University, 2025)
The development of magnetically recyclable photocatalysts for economic and green H2O2 synthesis from water and oxygen only is virtually unexplored. Magnetic recyclability makes possible cost-effective laboratory or industrial reuse of the catalyst. The present research shows that magnetically recyclable starch functionalized Fe3O4/Ag/Ag2O superparamagnetic nanocomposites are very good visible light photocatalysts for H2O2 formation. These nanocomposites were prepared by precipitating Ag/Ag2O fine-sized nanostructures on starch functionalized magnetite nanoparticles (SMNPs). HR-TEM, XRD, and XPS analysis results showed the formation of SMNPs dotted with fine-sized Ag/Ag2O nanostructures smaller than their quantum confinement regimes. A p-n heterojunction is formed between (n-type) starch functionalized magnetite and (p-type) Ag2O components. Enhanced charge separation and the presence of plasmonic Ag nanostructures on the SM component cause efficient oxygen reduction with high H2O2 formation rates. © 2020 Elsevier Ltd